2013
DOI: 10.1249/mss.0b013e31828e8f07
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physical Activity in Anorexia Nervosa and Treatment Outcome

Abstract: PA in patients with anorexia nervosa is underestimated by subjective assessment when compared with objective measurement. Only time spent in light PA, assessed objectively with AH, showed a negative association with improvement in eating disorder psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
4
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 34 publications
4
50
4
2
Order By: Relevance
“…They assumed that smoking cigarettes, anxiety and PA have an influence on weight gain, which could not be confirmed by the results. This was also affirmed by Alberti et al (2013), who compared objective and subjective measurement of PA in AN. They could show that accelerometry is sensible and specific in distinguishing between lying, sitting, standing and walking with different velocities, meaning that the acceleration of the device correlates with the energy expenditure and the walking velocity.…”
Section: Validation Of Accelerometrymentioning
confidence: 72%
See 1 more Smart Citation
“…They assumed that smoking cigarettes, anxiety and PA have an influence on weight gain, which could not be confirmed by the results. This was also affirmed by Alberti et al (2013), who compared objective and subjective measurement of PA in AN. They could show that accelerometry is sensible and specific in distinguishing between lying, sitting, standing and walking with different velocities, meaning that the acceleration of the device correlates with the energy expenditure and the walking velocity.…”
Section: Validation Of Accelerometrymentioning
confidence: 72%
“…Kostrzewa et al (2013) investigated how high activity levels are influenced by inpatient treatment and found that the PA level normalizes during treatment. Alberti et al (2013), however, showed that the more time spent in light PA at the beginning of the treatment, the less improvement can be seen in ED psychopathology at the end of therapy. Despite this, HLPA leads to long-standing consequences in recovery of leptin serum levels and body composition.…”
Section: Correlations Of Physical Activity Behaviour and Treatmentmentioning
confidence: 92%
“…It has been associated with increased risk of medical complications (e.g., overuse injuries, bone fractures, and cardiac complications) [67,68,69,70], higher rates of dropout from treatment programmes [71], longer inpatient treatment [72], poorer outcome [62], and quicker relapse [73]. It is also associated with greater severity of eating disorders [74] and general psychopathology, as well as specific personality features such as perfectionism and persistence [64]. It should be noted that many athletes may rely on their perfectionism, a trait associated with setting high goals and working hard to attain them [75], to help them succeed.…”
Section: Resultsmentioning
confidence: 99%
“…Compulsive exercise poses an obstacle for treatment progress (Solenberger, 2001; Carter et al, 2004; Dalle Grave et al, 2008). Many clinicians have therefore favored the prohibition of exercise during treatment; however, some studies have shown that supervised, moderate physical activity programs may be beneficial (Alberti et al, 2013; Kostrzewa et al, 2013; Sauchelli et al, 2015). The present study shows that compulsive exercise should not be addressed equally in all ED, and interventions incorporating physical activity programs should be adapted to the distinct ED diagnostic subtypes.…”
Section: Discussionmentioning
confidence: 99%